Dampak Manajemen Waktu dan Pelatihan Online terhadap Kinerja Karyawan Peran Pengalaman Kerja sebagai Variabel Mediasi - Lusi Endang Sri D; Dassucik Dassucik; Ahmad Hafas Rasyidi (Pusat Riset dan Inovasi Nasional, 2024)
This study explores the effect of Time Management (X1) and Online Training (X2) on Employee Performance (Y), with Work Experience (Z) acting as a mediating variable. This study uses Structural Equation Modeling (SEM) with Partial Least Squares (PLS) to analyze data from 96 sales employees at XL Fiberhome, Jember. The results reveal that Time Management and Online Training contribute significantly to Employee Performance, with Time Management showing a moderate direct effect and Online Training showing a slightly stronger impact. Fur-thermore, Work Experience was found to mediate the relationship between Time Management and Online Training and Employee Performance, indicating that employees with greater work experience can more effectively apply the skills acquired through time management and training. The findings of this study underscore the im-portance of integrating time management practices and continuous online training into organizational strategies to improve employee performance, especially in today's rapidly changing and flexible work environment. The sig-nificant direct and indirect effects observed in this study highlight the interrelatedness of these factors, offering new insights into how organizations can optimize performance through a combination of skill development and experience. These results contribute to the broader literature on employee performance by offering a compre-hensive model that accounts for the dynamics of evolving modern work practices. This study also provides practical recommendations for human resource management, emphasizing the need for organizations to invest in time management tools, online training platforms, and supportive work experiences to enhance productivity.